Carrier dynamics in ZnxCd1-xO films grown by molecular beam epitaxy. Issue 1 (May 2016) - Cheng, F J; Lee, Y C; Hu, S Y; Lin, Y C; Tiong, K K; Chou, W C
Abstract: In this work, the carrier dynamics in Zn1-x Cdx O thin films with different Cd contents grown by molecular beam epitaxy system have been investigated using photoluminescence and time-resolved photoluminescence measurements. The carrier lifetime can be estimated from the PL decay curve fitted by triple exponential function. The emission energy dependence and temperature dependence of the PL decay time indicate that carrier localization dominate the luminescence mechanism of the ZnCdO alloy semiconductor.